Food Supplementary Programmes Management Practice in Primary School in Negeri Sembilan, Malaysia - Md Yusoff, Md Razali (2008)
The purpose of the research is to determine the profiles of the Food Supplementary Program (RMT) teachers and to find the relationships between their knowledge, experiences, training and workload factors with the implementation of RMT management. A total of one hundred forty teachers from selected primary schools in Negeri Sembilan have been chosen to participate in this study. The selection of the respondents was made through a stratified random sampling technique. The instruments used in the study were teachers’ profile questionnaires, RMT management knowledge questionnaires and RMT management implementation questionnaires. The reliability of these instruments is 0.859 dan 0.949 respectively. The analysis of the content validity had been established by three experts. Majority of the respondents in the study were female teachers, age below 40 years old, Malays, with at least SPM qualification, with below twenty years of teaching experiences and have less than five years experiences in managing the RMT Program. Majority of them are also have the teaching workload between 21 to 30 periods per week, spending less than three hours a week in managing the RMT program and have one to two portfolios. Majority of the respondents have never attended any course on RMT and only a few were supplied with the RMT management manual. The level of teachers’ knowledge was at intermediate level (M = 18.4, SD = 3.4) and the level of the RMT management implementation was at excellent level (M = 3.9, SD = 0.5). The findings showed a positive but no significant relationship between teachers’ knowledge and the RMT management implementation (r = 0.181, p = 0.032). However, there was no significant relationship between teachers’ workload, teachers’ experiences with the RMT management implementation. The findings show that from the aspect of the RMT management implementation, the SJK schools have better RMT management implementation than SK school. (t = 3.451, df = 138, p < 0.05 ). In conclusion, although the RMT management implementation is at excellent level, there were some schools did not follow the correct procedure. It was due to the lack of standard procedures required. Therefore, the standard procedures of managing the Food Supplementary Program should be made compulsory as an act and implemented in all schools. Besides, all the selected teachers should undergo the appropriate training on how to manage the program based on an act provided.